The new high school as a producer of inequalities: A literature review - Santos, Carolina Fonseca Nonato; Lima, Ubirajara Couto (Seven Editora, 2023)
In 2017, Law No. 13,415 was sanctioned, which brings in its text the reform of High School, which in Brazil corresponds to the last three years of basic education and is characterized by the completion of the school cycle. The modification of the guidelines for this stage of education raised controversies and debates. Therefore, this article aims to analyze the main changes proposed by the New High School and how they are affecting students' education. The adopted methodology was a narrative literature review, and for this, 8 articles were selected as the main sample, using inclusion and exclusion criteria. Based on the results, the reform was pointed out as a possible producer of inequalities that deepen the division between students from public and private schools, increasing the disparity in access to relevant content for the education of young people through elective subjects. Thus, for an effective High School, it is necessary to create public policies that guarantee equity in education, such as the offer of extracurricular courses and investments in technology and teacher training. DOI:https://doi.org/10.56238/ptoketheeducati-064